Hemodynamic Effects of Concomitant Mitral Valve Surgery and Left Ventricular Assist Device Implantation. Issue 4 (April 2020) - Imamura, Teruhiko; Nnanabu, Jerry; Rodgers, Daniel; Raikehlkar, Jayant; Kalantar, Sara; Smith, Bryan; Nguyen, Ann; Chung, Ben; Narang, Nikhil; Ota, Takeyoshi; Song, Tae; Burkhoff, Daniel; et al.
Abstract : There are conflicting data regarding whether concomitant mitral valve surgery (MVS) at left ventricular assist device (LVAD) implantation is beneficial. This study aimed to assess the hemodynamic effects of concomitant MVS. Of all 73 enrolled patients, 44 patients had undergone concomitant MVS and 29 patients had not. Before LVAD implantation, MVS group had higher pulmonary capillary wedge pressure ( p = 0.04). After LVAD implantation, MVS group had higher mean pulmonary artery pressure and cardiac output (CO). During the hemodynamic ramp study, MVS group had steeper CO slopes (0.18 [0.13 0.28] vs. 0.15 [0.08, 0.20] L/min/step; p = 0.04) at incremental LVAD speed and achieved a higher CO at the optimized set speed (5.5 [4.7, 6.9] vs. 4.9 [4.0, 5.7] L/min; p = 0.03). One-year freedom from death or heart failure readmission was statistically comparable between the two groups (61% vs. 80%, p = 0.20). Thus far, after LVAD implantation and concomitant MVS, patients had increased pulmonary hypertension, despite having higher CO and a better response of CO at incremental LVAD speed. The implication of hemodynamic features after concomitant MVS on clinical outcomes warrants further investigation. Abstract : Supplemental Digital Content is available in the text.